Le Guérisseur : Investigating the Therapeutic Qualities of Water as a Catalyst for healing in an Urban Oncology Wellness Treatment Centre - Botes, Nico (University of Pretoria, 2019)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2019.